Karakteristik Pembakaran Premixed Minyak Fame (Fatty Acid Methyl Ester) - Defmit B.N. Riwu; Dominggus Adoe; Reinaldy Weo (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2021)
Advances in technology and the times have caused the human need for energy to increase. This condition has an impact on the availability of fuel oil which is decreasing and will run out. To anticipate and prevent these problems, new alternative energy sources are needed as a substitute for energy sources that cannot be replaced. One alternative energy is FAME (fatty acid methyl ester) oil. FAME is a type of fatty acid ester derived by transesterification of fats with methanol. This research was conducted to determine the combustion characteristics of premixed FAME oil in the form of flame temperature and combustion speed. The results of the study, the greater the equivalence ratio, the smaller the flame temperature and combustion speed. This is because less air is available to burn the fuel. On the other hand, the smaller the equivalence ratio, the higher the flame temperature and combustion speed. This is because more and more air is available to burn the fuel. And at the time of equivalence ratio = 0.96, combustion is rich in air and close to the stoichiometric combustion. The angle of fire obtained is directly proportional to the speed of combustion.